The Role of Tourism Development Projects in Preserving the Tangible Cultural Heritage of Sharjah Emirate: Studying the Projects of Sharjah Institute for Heritage - Alsouqi, Hamda; Jamhawi, Monther; AbuElEnain, EmadEddin (Al-Adab Journal, 2024)
The tangible cultural heritage is considered one of the most important economic resources, of which tourism is one of the most important aspects. Indeed, heritage, whether in its tangible or intangible form, is one of the cultural tributaries that form the collective memory of any nation or people. The Emirate of Sharjah has taken care of its heritage and preserved it through the enactment of regulatory and conservation laws and legislation. Its institutions have also drawn up strategic and developmental plans for heritage areas and museums. Along with marketing and promoting tourism to them. Despite the efforts of the Emirate of Sharjah through its institutions to plan and implement tourism projects based on the sustainability and preservation of the tangible cultural heritage, there is a lack of studying the impact of these projects on preserving the heritage. Hence, it was necessary to study these projects. The study relied on the descriptive analytical approach. The study was conducted on a sample of (144) single professionals in tourism companies and hotel employees in the Emirate of Sharjah working in the Department of Tourism Promotion and Reservations. The sample also included employees of the Sharjah Heritage Institute. The results concluded that there is a strong correlation between the variable of tourism development projects and its impact on preserving the tangible heritage in the Emirate of Sharjah, as the correlation coefficient reached (0.890). which is a strong direct relationship and is a statistically significant value. Besides, it indicates the association between the independent variable and the dependent variable. The study also recommends developing existing laws and legislation and issuing guiding instructions for methods and methods of preserving heritage by following what science provides in this regard, especially the use of artificial intelligence techniques. Together with, the development of periodic control methods based on modern technology, greater adherence to guiding standards to reduce pollution. Moreover, the adoption of means of transport that preserve more tangible heritage.